Khauf and Raja’ as Psychotherapy for Heart Disease from the Perspective of Ibn Qayyim Al-Jauziyah - Aris Saputra (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2025)
This research stems from the spiritual drought experienced by a servant who relies on material things, which leads to spiritual illness that affects both worldly and afterlife matters. Because of placing hope in other than Allah, rather than hoping in Allah (raja’). According to Ibn Qayyim, raja’ must be accompanied by khauf (fear), which makes a servant cautious and prevents sin. The purpose of this study is to analyze Ibn Qayyim's thoughts on the treatment of heart disease through khauf and raja’. This study is a literature study that collects and analyzes data from various literature to explore Ibn Qayyim's understanding. The results of the study show that, first, khauf and raja' motivate a servant to do good and avoid sin. Second, heart disease occurs when the heart fails to perform its function of drawing closer to Allah, which is caused by false hopes and a lack of fear. Third, khauf and raja' can function as therapy if practiced through righteous deeds such as prayer, fasting, charity, and avoiding sin. From these findings, khauf and raja' must be practiced in daily life to heal the heart and strengthen spiritual well-being.